Evaluation of Synthetic Osteochondral Implants - Cook, James L.; Kuroki, Keiichi; Bozynski, Chantelle C.; Stoker, Aaron M.; Pfeiffer, Ferris M.; Cook, Cristi R. (The Journal of Knee Surgery, 2014)
This translational animal model study was designed to assess function, bone ingrowth and integration, and joint pathology associated with two different synthetic, bilayered osteochondral implants over a 3-month period after implantation into the femoral condyles of dogs. SynACart-Titanium (n = 6) and SynACart-PEEK (n = 6) (Arthrex, Naples, FL, and Sites Medical, Columbia City, IN) implants were press-fit into the lateral or medial femoral condyle (alternating location) of purpose-bred adult research dogs. Dogs were humanely euthanized 3 months after surgery and the operated knees were assessed radiographically, arthroscopically, grossly, and histologically. Based on all assessments, both types of implants were well tolerated and safe with no evidence for infection, migration, or rejection. Half of the SynACart-PEEK implants showed radiographic and histologic evidence of poor incorporation with all of these being in the lateral femoral condyle. SynACart-Titanium implants were considered effective in terms of integration into bone, lack of damage to surrounding and apposing articular cartilage, and maintenance of implant integrity and architecture for the duration of the study.
Keywords: knee; osteochondral; dog; femoral condyle; synthetic